FRI0483 Variation of antiphospholipid antibody (APL) titers in patients with persistent antiphospholipid antibodies. (23rd January 2014) - Vegas, C.; Martinez, M. J.; Tellez, R.; Tramon, P.; Rodriguez, M. J.; Palacios, C.; Sanchez, O.; Serrano, C.
Abstract : Background: APL have been closely associated with venous and arterial thrombosis. For the diagnosis of Antiphospholipid Syndrome (APS) clinical criteria are needed (thrombotic events and/or repeated abortions) and a persistently positive laboratory criteria (Lupus Anticoagulant–LA-, AntiCardiolipin Antibodies –ACA- or antiβ2GPI). Nevertheless these markers are not specific for APS. Objectives: Relate variations of titers in patients with persistently positive APL. Methods: 237 sera which had at least one ACA and/or antiβ2GPI positive determination (ELISA QUANTA Lite®-INOVA Diagnostics®-manufacturer cut off: >20 MPL/GPL/SMU/SGU) were prospectively evaluated. Those which tested positive at least two times for any of these antibodies were selected and monitored for a mean period of 24 months (2011-2012). Variation is defined as a change in semiquantitative subset: Low positive (20-50 MPL/GPL/SMU/SGU), Medium positive (50-80 MPL/GPL/SMU/SGU) and High positive (>80 MPL/GPL/SMU/SGU) when comparing the first result to the endpoint. Statistical analysis was performed with GradPhad®. Results: 49 out of 237 (20.67%) had at least 2 samples with one or more positive antibody. Mean interval between tests was 6 weeks. There were 24 patients and the (mean visits per patient: 2.1). Clinical diagnosis were: 8 Primary APS (33%), 7 with multiple diseases without Trombotic/Obstetric events (30%), 5 (21%) with Thrombotic/Obstetric events without APS diagnosis and 4 Lupus (16%). 26 sera were positive for ACA IgM (53%), 22 forantiβ2GPI IgM (49%), 13 for ACA IgG (30%) and 8 for antiβ2GPI IgG (16%). Of the 49 sera, 27 (58%) had 2 or more positive antibodies -the most frecuent association was double positivity ACA IgM and antiβ2GPI IgM (31%) -and 21 (42%) had 1 positive antibody in the first sample (most frecuently ACA IgM (53%). At the first determination, 17 (32%) tests had Low positive antibodies, 19 (27%) had Medium positive and 18 (41%) had High positive antibody. 72% of the sera were stable in the same subset, independently of the original titer and type of antibody. In our sera, 47% which had persistent titers of APL in high positive levels were diagnosed APS. 90% of APS sera were stable in this titers and the 70% had 2 or more antibodies. Conclusions: 1) In our study, persistent APLs were not frecuent (20.67%). 2) Although APLs are predominantly in APS, also there is a high prevalence of persistent antibodies in patients without thrombotic/obstetric events and Lupus. 3) IgM is the most prevalent isotype antibody both associated (ACA IgM- antiβ2GPI IgM) and isolated (ACA IgM). 4) Regardless of the initials levels, most of the APLs values that no disappear are maintained in the same levels. 5) Persistent APLs in primary APS do not fluctuate. This could be useful to leave monitoring patients whom were diagnosed APS. References: Comarmond C, Cacoub P. Antiphospholipidsyndrome: From pathogenesis to novel immunomodulatory therapies. Autoimmun Rev. 2012 Dec 30 D Erkan, W J M Derksen, V Kaplan, L Sammaritano, S S Pierangeli, R Roubey, M D Lockshin. Real world experience with antiphospholipid antibody tests: how stable are results over time? Disclosure of Interest: None Declared